ANALYSIS OF FARMER BEHAVIOR IN SELECTING FERTILIZER FOR IMPROVING AGRICULTURAL PRODUCTIVITY (Case study in Sukoharjo Regency) - Tria Rosana Dewi; Irma Wardani; Sudarwati Sudarwati (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2020)
Efforts to increase the productivity of agricultural products are influenced by many factors, there are several factors that are highly dependent on the efforts made by humans, such as, the preparation of land, fertilizer selection, the application of proper farming procedures, the right way of harvesting and good post-harvest processing.The research to be conducted aims to determine the effect of quality, packaging and fertilizer prices on fertilizer selection to improve the productivity of agricultural products. The research used survey method, which is analyzing farmer behavior in choosing fertilizer. Technique of collecting data through questioner given to respondent. Sampling is done by random sampling. Samples in this study were 100 farmers from 12 sub-districts in Sukoharjo District. Data analysis techniques used to test the hypothesis is multiple regression analysis, t test, F test and determinant coefficient with SPSS program.The result of this research is that there is a significant influence between quality variable (X1), packaging (X2), and price (X3) together on fertilizer selection to increase productivity of agricultural product. While partially there is no significant effect between the quality (X1) on the selection of fertilizers to improve the productivity of agricultural products. But there is a significant influence between packaging (X2) and price (X3) on fertilizer selection to increase agricultural productivity. The contribution of the three variables, namely quality, packaging and fertilizer price to the selection of fertilizer to increase the productivity of agricultural products by 43.50%. While the rest equal to 56,50% influenced by other variable outside this research. Keywords: Selection of Fertilizer, Productivity.